The African and Asian ivory markets in Europe: a survey of five countries - Daniel Stiles; Esmond Martin (Pachyderm)
This artilce reviews matiersl presented in report that covered the ivory markets in the five European countires wihc appear to be the most active in ivory importation, craft presentations and sales. (Stiles and Martin 2000, 2002, 2003). Sources and costs of ivory, crafts people; shops and the retail market and prices in the UK, France, Spain, Italy and Germany are assessed. This study suggets the UK and German markets are relatively significant but consider that thos of France, Italy and Spain are small. Germany and France have legal active ivory craftsmen and ivory stockpiles for such use. Most of the items seen were ivory items imported prior to 1989, or were legal antique items imported since then. Some East Asian and African worked items from later ivory were seen, but this illegal material is considered to be very minor. The author suggest the demand for tusks, legal otr illegal, is small and the five surveyed countries 'seem to be complying well with CITES'.